Rekonstruksi Peran Orang Tua dan Guru Dalam Pendididkan Islam Pasca Pandemi - Haryati Haryati; Supardi Widodo; Syarifuddin Ondeng; Munawir Kamaluddin (Peneliti.net, 2023)
Reconstruction means returning to the way it was or rearranging (depicting) again. Reconstruction of the role of parents and teachers in Islamic education refers to the best human beings and the best generation, namely: the Prophet Muhammad SAW, companions and afterwards by understanding the concept of Islamic Education, especially the role of parents and teachers in educating children/students from various Islamic reference sources. Islamic education is only one aspect of Islamic teachings as a whole. Therefore, the purpose of Islamic education is inseparable from the purpose of human life in Islam, namely to create personal servants of Allah who always fear Him and can achieve a happy life in this world and the hereafter. The reconstruction of the role of parents in Islamic education refers back to the concept of Islam in children's education (Tarbiyyatul Aulad fil Islam), namely understanding and practice related to marriage, the laws surrounding birth, the causes of delinquency and its management, the responsibility of educators (in faith education, moral, reason, psychology, social and sex), methods and means, basic rules in children's education as well as effective educational facilities. Reconstructing the teacher's role in Islamic Education by carrying out a role for their students, namely the role of the teacher as a facilitator and as a spiritual father must be able to provide breakfast for the soul with knowledge, moral education and justify it based on a sense of responsibility and compassion. Then the process of teaching and educating a teacher should be a thorough and comprehensive education in all aspects of child development (cognitive, affective and psychomotor) that is not one-sided and strives for a variety of methods, means, media, an understanding of the character of students and an understanding that every child is special and every child is unique. Teachers must be able to be role models, provide guidance and encouragement to their students.